The Relationship Between Knowledge Level and Diet Behavior in Hypertension Patiens at Lepak Public Health Center - Maruli Taufandas; Apriani Susmita Sari; Leni Syne Andriani; Emdat Suprayitno (MBUnivPress, 2022)
Hypertension is an increase of systolic blood pressure at least 140 mmHg or diastolic pressure atleast 90 mmHg. Factors that influence hypertension are consumption of foods generally contain a lot of salt, high fat and high sugar. Bad diet behavior and knowledge level can influence this. To determine the relationship of level knowledge and diet behaviour of hypertension patients in Lepak Primary Health Centre.The design study using a quantitative analytical observational with cross sectional approach.The number of samples were 59 respondents and taken by using purposive sampling approach.The statistical test used in this study is the Spearman Rank test.There is a relationship between level knowledge with diet behavior of hypertension patients, with p value= 0,000 (p <0.05). The next test to determine the strength of the correlation between the level of knowledge and behavior with a value of 0.373, which means that the strength of the category relationship is quite strong and the direction of the relationship is positive.High knowledge and more positive attitudes have a good impact for hypertension patients, so that it can be recommended for patients to improve knowledge and attitudes to become the basic for following basi s to recommended diet.